(untitled) (Scientific journal of the Fergana State University, 2024)
It is known that the proper organization of independent education of students in higher education institutions, creation of tasks in modern forms and its control, and evaluation in an optimal form are one of the urgent problems in today’s educational process. Therefore, in this article, one of the modern forms of organizing independent education will be highlighted. Also, in order to develop the readiness of future elementary school students for professional activities, information is provided about the content and advantages of organizing their independent education based on problem-based education. In addition, examples of problematic situations encountered in pedagogical activity were given, and its application in the process of independent education was shown in practical terms. At the same time, it was emphasized that the main goal of problem-based education is students’ independent assimilation of new knowledge by choosing the optimal solution to a problem situation.